Unveiling ZrO2/natural zeolite catalytic performance on hydrocracking palm oil mill effluent residue - Junifa Layla Sihombing; Herlinawati Herlinawati; Ahmad Nasir Pulungan; Agus Kembaren; Gimelliya Saragih; Harmileni Harmileni; Rahayu Rahayu; Ary Anggara Wibowo (Pascasarjana Universitas Negeri Medan, 2023)
Palm oil mill effluent (POME) is the largest liquid waste from crude palm oil production. This liquid waste still contains a lot of chemical components, solid deposits, and oil which is dangerous if released directly into the environment. The residual oil and grease components contained in POME can be further extracted and converted into fuel fractions. This study investigates the conversion of residual oil from POME into fuel fractions through hydrocracking. A ZrO2/Sarulla natural zeolite (SNZ) catalyst was used, characterized by a particle size of 1-1.5 µm, a surface area of 73.3 m2/g, a pore volume of 0.161 cc/g, and a pore diameter of 3.35 nm. The effect of catalyst mass was studied, with the total conversion increasing to a certain extent with increasing catalyst mass, however, an increase in coke formation decreased the product yield. The highest gasoline fraction selectivity was obtained with a catalyst mass of 0.09 wt% ( 42%), while the kerosene fraction was most obtained with a catalyst mass of 0.15 wt% ( 40%). The liquid product with a catalyst mass of 0.15 wt% had the highest HHV of 44.2 MJ/kg, a 12% increase from the HHV of POME oil residue (39.4 MJ/kg). The results demonstrate the potential of using residual oil from POME as a source for fuel production and the use of natural zeolite-based catalysts as hydrocracking catalysts.Keywords: Biofuel; Hydrocracking; Natural zeolite; Oil extracted; Palm oil mill effluent